Disparity and Multimorbidity in Heart Failure Patients Over the Age of 80 - Anna Blach BS; Amanda Pangle BS; Gohar Azhar MD; Jeanne Wei MD, PhD (Gerontology and Geriatric Medicine, 2022)
Background: Healthcare is currently struggling to provide access and coverage for an increasingly diverse aging population who frequently have multiple co-morbid conditions complicating their care and medical management. Methods: This retrospective study analyzed the prevalence and distribution of common co-morbid conditions (hypertension, dyslipidemia, dementia, and diabetes mellitus) in 316 elderly heart failure patients (age range 80–103; mean 87 ±4.9). Results: Chart review analysis showed a racial distribution of 65 African American versus 251 Caucasian patients (21 vs. 79%). Hypertension was comparable in both groups (98.5% African American vs. 92.4% Caucasian). Dyslipidemia, diabetes and dementia diagnoses were all approximately 20% higher in African American versus Caucasian patients. The concurrent presence of all four conditions was approximately three times more prevalent in African Americans (18.5%) versus Caucasians (7.2%). Conclusion: Our study is unique for studying disparity in octogenarian and nonagenarians residing in a rural setting. Our results also highlight the importance of making a special effort to engage older African American patients in seeking healthcare. In addition, strategies must be designed to reduce barriers that impede access and availability of resources and clinical care, especially in economically underserved regions of the country.